2016
DOI: 10.1208/s12249-016-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and In Vitro/In Vivo Evaluation of Ultra-Thin Mucoadhesive Buccal Film Containing Fluticasone Propionate

Abstract: ABSTRACT. Fluticasone propionate is a synthetic corticosteroid drug distinguished by its potent antiinflammatory action with low systemic side effects in comparison to other corticosteroids making it a potential drug for local buccal delivery. The aim of the present study was to design mucoadhesive buccal film containing fluticasone that is aesthetically acceptable and could maintain local drug release for a sustained period to manage the sign and symptoms of severe erosive mouth lesions. Solvent casting techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…The findings revealed that the produced films were functional, mucoadhesive, flexible, and stable, with the potential for treating various intraoral diseases [123]. EC-based mucoadhesive buccal films containing fluticasone formulated by solvent casting technique showed acceptable physicochemical properties, homogenous drug distribution, adequate mucoadhesion time, moderate swelling, and sustained drug release up to 12 h [124]. The objective of another study was to develop a two-layered buccal mucoadhesive system consisting of a highly water-soluble drug (i.e., risedronate).…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 99%
“…The findings revealed that the produced films were functional, mucoadhesive, flexible, and stable, with the potential for treating various intraoral diseases [123]. EC-based mucoadhesive buccal films containing fluticasone formulated by solvent casting technique showed acceptable physicochemical properties, homogenous drug distribution, adequate mucoadhesion time, moderate swelling, and sustained drug release up to 12 h [124]. The objective of another study was to develop a two-layered buccal mucoadhesive system consisting of a highly water-soluble drug (i.e., risedronate).…”
Section: Applicability Of Ec In Pharmaceutical Formulationsmentioning
confidence: 99%
“…Sufficient mucoadhesion is one of the most important criteria which a film must comply with application into the oral cavity. Typical polymers used as mucoadhesive components are gelatin, chitosan [66], pullulan [67], guar gum [68], xanthan gum [61], sodium carboxymethylcellulose [69], hydroxypropylcellulose [70] and sodium hyaluronate [71]. Various natural polysaccharides show mucoadhesive properties such as psyllium [72], okra [73] and certain rice varieties with a high amylose content [74].…”
Section: Local and Systemic Drug Deliverymentioning
confidence: 99%
“…In a similar way, fluticasone propionate was formulated for localized buccal delivery through a mucoadhesive buccal film formulation composed of ethylcellulose and other polymeric blends. Films based on ethylcellulose were selected as the best performing with desirable sustained release characteristics and potential therapeutic efficacy (Ammar et al, 2017).…”
Section: Macro-structured Delivery Systems Fabricated From Ethylcellumentioning
confidence: 99%